Quality Assurance of Intermediate Qualifications in the Pharmaceutical Industry - Arbizu Echavarri, Francisca (2018)
This research—included in the "Professional Qualifications of the Pharmaceutical Industry Within the Framework of the LOGSE” thesis—responds to the need to verify the relevance, quality, and effectiveness of the degrees of Technician in Manufacturing Operations of Pharmaceutical Products, (TOFPF), at the secondary level, and Higher Technician in Manufacturing of Pharmaceutical and Related Products (TSFPA), in higher education. Both degrees were created in 1993, in response to European Directives and Spanish legislation, dated as of 1991, on Good Manufacturing Practices of Medications, for human, veterinary, and cosmetics use, which requires manufacturers to have sufficient competent staff, with appropriate qualifications in all their manufacturing facilities to achieve the objective of pharmaceutical quality assurance. The article includes the evaluation of the quality of the TSFPA degree from its identification and design mechanisms (1991-1994), as well as the results and effects of its implementation and development (1995-2015), and even its revision (2004-2017) and impact providing qualitative and quantitative empirical evidence, according to the reference indicators proposed by the Recommendation on the establishment of a European Framework of Reference for Quality Assurance in Professional Training.